Ekowisata Bahari dan Wisata Olahraga Bahari di Desa Olele: Studi Pendahuluan - Fadli, Moh; Rahayu, Tandiyo; Setyawati, Heny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to obtain a general overview of marine ecotourism and marine sports tourism in Olele Village. Applying qualitative description methods, this research uses interview techniques, observation, and literature study for data collection. This research shows that sports tourism activities are in the marine ecotourism area in Olele Village. Types of sports activities, namely snorkeling and diving. In conclusion, there are tourism activities in the marine ecosystem area in Olele Village. Keywords: ecotourism, sports tourism, marine sports